Missing Mechanism Information. - Tryon, Warren W. (American Psychologist)
A commentary on an article by A. E. Kazdin that appeared in the American Psychologist, 2008, vol. 63, pp. 146–159. In the article, Kazdin suggested that one strategy for advancing the psychotherapy research knowledge base, enhancing patient care, and narrowing the wide gap between research and practice was to explore the mechanisms of therapeutic change. The writer contends that Kazdin neglected to mention a wide and rapidly increasing body of literature on parallel distributed processing–connectionist neural network models of cognition, affect, and behavior that offer psychologically pertinent data on causal mechanisms.